2011
DOI: 10.4066/amj.2011.823
|View full text |Cite
|
Sign up to set email alerts
|

Teleconferencing in Medical Education: A Useful Tool

Abstract: Education and healthcare are basic needs for human development. Technological innovation has broadened the access to higher quality healthcare and education without regard to time, distance or geopolitical boundaries. Distance learning has gained popularity as a means of learning in recent years due to widely distributed learners, busy schedules and rising travel costs. Teleconferencing is also a very useful tool as a distance learning method.Teleconferencing is a real-time and live interactive programme in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 18 publications
0
49
0
2
Order By: Relevance
“…The bene t of videoconferencing and e-learning systems in medical education has previously been shown, with the opportunity of not only delivering lectures or tutorials, but to present invasive procedures as well. 16,17 In addition, an online focus group qualitative study found a good acceptance rate of synchronized online learning by students during the COVID-19 pandemic. 18 Both students and instructors found our virtual course effective and acceptable in replacing in-person learning and bed-side sessions to keep education continuous during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The bene t of videoconferencing and e-learning systems in medical education has previously been shown, with the opportunity of not only delivering lectures or tutorials, but to present invasive procedures as well. 16,17 In addition, an online focus group qualitative study found a good acceptance rate of synchronized online learning by students during the COVID-19 pandemic. 18 Both students and instructors found our virtual course effective and acceptable in replacing in-person learning and bed-side sessions to keep education continuous during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The biggest barrier to participation was poor audio quality due to loud ambient sounds such as patient alarms and the inability to hear conversations due to distance from the conference speaker. Care should be taken to configure the speaker closely to the person speaking in the unit to try to minimize audio interference that can take away from the learning environment [ 25 ]. One method found to improve sound was to place the Bluetooth conference speaker on a rolling cart in the middle of the rounding team, allowing it to be easy moved closer to the team member speaking.…”
Section: Discussionmentioning
confidence: 99%
“…Video links have already been introduced in certain specialities including psychiatry and neurology to deliver undergraduate17 18 and postgraduate teaching 19. The main advantages observed included removing geographical barriers for national and international experts to deliver teaching sessions and eliminating the cost of travelling 18 19.…”
Section: Discussionmentioning
confidence: 99%